Prediction of buffalo bull fertility based on sperm motion traits, function tests and expression of heparin binding protein - SINGH, A K; BRAR, P S; CHEEMA, RANJNA S; KUMAR, PRADEEP (The Indian Journal of Animal Sciences, 2017)
Selection of good fertility bulls is a challenge since large variations exist in the result of tests applied for semen evaluation. Therefore, the present study was undertaken to predict the fertility of buffalo bulls on the basis of sperm motion traits, function tests and expression of heparin binding protein (HBP). Both fresh and frozen semen from breeding Murrah buffalo bulls (30) were procured from 2 government bull farms. The frozen-thawed semen was used to evaluate first service conception rate (FSCR), CASA-based motility (total and progressive) and function tests (HOST, acrosome reaction and DNA integrity). On the basis of FSCR, all bulls were divided into 3 groups, viz. good fertility bulls (GFB, >50%), average fertility bulls (AFB, 30-49.9%) and poor fertility bulls (PFB, <30%). Additionally, fresh and frozen-thawed semen were analyzed for quantification and characterization of HBP through affinity chromatography. CASA based total motility and acrosome reaction were significantly higher in GFB as compared to their counterparts. No significant difference between good and average fertility bulls was observed for percent HOST and progressive motility. The HBP was 6.6±0.2 mg/ml, 0.63±0.02 mg/109 sperms and 0.36±0.02 mg/109 sperms in seminal plasma, fresh- and frozen-thawed spermatozoa, respectively. Although, there was no significant difference in the quantity of total HBP in semen with respect to bull fertility, a specific trend definitely existed. The HBP peak was separated into proteins of 135, 100, 75, 65, 48, 45, 40, 37, 31, 28, 26, 20, 18, 16 and 11 kDa in seminal fluid. Overall, the purified HBP indicated the presence of 65, 31, 20 and 11 kDa proteins in seminal plasma, fresh- and frozen-thawed sperm extracts of good fertility bulls and seemed to be candidate proteins to predict buffalo bull fertility. It was concluded that CASA-based total motility, acrosome reaction and purified HBP-65, HBP-31, HBP-20 and HBP-11 in buffalo bull sperm could be used for differentiation of good fertility bulls from poor fertility ones.